Chinese Altay sheep adapt to seasonal fluctuations in forage nutrients by changing physiological status and rumen microbial community structure - Ma, Mingyu; Zhang, Peng; Xu, Zhenzi; Li, Shu; Li, Sijin; Lu, Qicheng; Zhang, Wenju; Li, Yuanyaun (Frontiers in Microbiology, 2025)
IntroductionAs the primary nutritional source for grazing livestock, natural forage directly influences changes in physiological status and rumen microbial community structure owing to seasonal variations in its nutritional composition. However, the physiological and rumen microbial community adaptations of Chinese Altay sheep in response to seasonal variations in forage nutrition remain unclear.MethodsTherefore, this study systematically evaluated the effects of seasonal dynamics in forage nutrition on growth performance, nutrient digestibility, blood parameters, rumen fermentation characteristics, and rumen microbiota in grazing Chinese Altay sheep. A total of 18 grazing Altay growing ewes with similar body weight, age, and good health condition were selected for the experiment. During four typical seasons (spring green-up, summer lush, autumn withering, and winter dormancy), Altay sheep were administered C32 slow-release capsules, with concurrent collection of forage, feces, blood, and rumen content samples.ResultsThe results indicated that the nutrient content of forages was abundant in summer and autumn, leading to high feed intake by the Altay sheep. This enabled the animals to promote weight gain through enhanced nutrient digestibility and rumen fermentation efficiency. Blood biochemical parameters of the Altay sheep varied in response to seasonal changes and forage nutrient availability. The results demonstrated that during summer, grazing Altay sheep exhibited a decline in antioxidant capacity, as well as reduced concentrations of Immunoglobulin A (IgA), Immunoglobulin G (IgG), and Immunoglobulin M (IgM). In autumn, significant enrichment of Bacillota and NK4A214_group was observed in the rumen of grazing sheep, which contributed to enhanced nutrient acquisition and thereby promoted fat deposition. In winter, Rikenellaceae_RC9_gut_group and Prevotellaceae_UCG-003 were significantly enriched in the rumen of grazing sheep, facilitating fiber decomposition and the production of volatile fatty acids (VFAs).Discussion and conclusionThis microbial adaptation helped the animals cope with nutrient scarcity by meeting their nutritional requirements. In conclusion, Altay sheep adapted to seasonal forage and environmental fluctuations through coordinated changes in feed intake, blood parameters, and rumen microbiota, thereby ensuring their survival.